Pathway-specific GABAergic inhibition contributes to the gain of resilience against anorexia-like behavior of adolescent female mice - Aoki, Chiye; Santiago, Adrienne N. (Frontiers in Behavioral Neuroscience, 2022)
Anorexia nervosa (AN) is one of the most debilitating mental illnesses that emerges during adolescence, especially among females. AN is characterized by severe voluntary food restriction and compulsive exercising, which combine to cause extreme body weight loss. We are using activity-based anorexia (ABA), an animal model, to investigate the neurobiological bases of vulnerability to AN. We provide a mini-review of recent findings from the Aoki Lab that point to the cellular and molecular underpinnings of three ABA phenomena: (1) age-dependence of ABA vulnerability; (2) individual differences in the persistence of ABA vulnerability during adolescence; (3) GABAergic synaptic plasticity in the hippocampus and the prefrontal cortex that contributes to the suppression of the maladaptive anorexia-like behaviors. We also include new data on ABA-like behavioral consequences of cell type-specific knockdown of a GABA receptor subunit, alpha4 in dorsal hippocampus. The data also explain why targeting just a single neurotransmitter system, such as of GABA, may have only limited efficacy in treating AN, since boosting the GABAergic system could suppress the maladaptive behavior of over-exercising but also suppress food consumption. A sub-anesthetic dose of ketamine may be the magic bullet, since s single injection of this drug to mid-adolescent female mice undergoing ABA induction enhances food consumption and reduces wheel running, thereby reducing body weight loss through plasticity at excitatory synaptic inputs to both excitatory and inhibitory neurons. However, the same treatment is not efficacious during late adolescence and multiple dosing of ketamine suppresses ABA vulnerability only partially. This caveat underscores the importance of conducting behavioral, synaptic and molecular analyses across multiple time points spanning the developmental stage of adolescence and into adulthood.